2011
DOI: 10.1111/j.1365-2125.2011.03988.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strong CYP2D6 and 3A4 inhibitors, paroxetine and ketoconazole, on the pharmacokinetics and cardiovascular safety of tamsulosin

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Tamsulosin metabolism involves both CYP2D6 and 3A4. However, data on potential drug-drug interactions between tamsulosin and inhibitors of CYP2D6 and 3A4 are limited and information on potential pharmacodynamic consequences of such pharmacokinetic interactions is missing. WHAT THIS STUDY ADDS• This study provides information on the drug-drug interactions of tamsulosin with strong CYP2D6 and strong CYP3A4 inhibitors after single dose administration in healthy subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 31 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…The selected study set consisted of 53 separate DDI studies taken from 46 publications between 2005 and 2015, which included 971 subjects with systemic ketoconazole exposure (Table ). A majority of the studies were conducted at study centers in the United States and Germany (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The selected study set consisted of 53 separate DDI studies taken from 46 publications between 2005 and 2015, which included 971 subjects with systemic ketoconazole exposure (Table ). A majority of the studies were conducted at study centers in the United States and Germany (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The differences observed in the present study are similar to those reported in a previous drug-drug interaction study with paroxetine, a potent CYP2D6 inhibitor. 10 Generally, CYP2D6 enzymatic activity can be expressed in terms of 4 phenotypes: PM, intermediate metabolizer (IM), extensive metabolizer (EM), and ultra-rapid metabolizer. The CYP2D6*10 allele is associated with reduced substrate affinity, 8 and many in vivo studies have shown that the metabolic capacity of homozygous CYP2D6*10 is between the capacities of EMs and PMs.…”
Section: Discussionmentioning
confidence: 99%
“…6 In a recent study, coadministration with a potent CYP3A4 inhibitor, ketoconazole, caused a 2.2-and 2.8-fold increase in the C max and AUC of tamsulosin, respectively. 10 Thus, it is possible that genetic polymorphisms in CYP3A4 or CYP3A5, which are considered to have similar substrate specificity, influence tamsulosin pharmacokinetics. To date, more than 19 CYP3A4 variant and subvariant alleles (*1B through *21) have been identified (http:// www.cypalleles.ki.se/cyp3a4.htm); however, there is no consensus on the direct functional correlations of CYP3A4 polymorphisms, which have only minor to moderate clinical importance because of their low allele frequencies and limited alterations on enzyme expression or catalytic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although antiplatelet and protective endothelium effects of sertraline have been reported [24], the results from three currently available epidemiological studies assessing the risk of MI in patients treated with SSRIs are controversial with regard to a potential beneficial effect of SSRIs on CVD risk in depressed patients. One study confirmed that sertraline caused concentration-dependent dilation in reconstructed arteries [22], [25]. A high dose of sertraline was able to fully reverse the level of vascular constriction caused by all types of vasoconstrictors.…”
Section: Introductionmentioning
confidence: 87%